Hubungan Antara Kepuasan Pasien BPJS Rawat Inap Terhadap Mutu Layanan Keperawatan Di Rumah Sakit Umum Daerah Salatiga - David Nakka Gasong; Venti Agustina; Clara Valentina (Jurnal Keperawatan Muhammadiyah, 2023)
Background Patients that participated in BPJS have voiced several grievances about the healthcare services offered to them, particularly in hospitals. Patients frequently express dissatisfaction with the time, availability of inpatient rooms, care, and nurse services provided to BPJS patients because they fall short of their expectations. Location for analyzing the association between the Salatiga Regional General Hospital's inpatient room's nursing services quality and BPJS patient satisfaction. Descriptive correlation research design cross sectional is the methodology employed. The population of this study, which was carried out in August 2022, included inpatient BPJS patients. 100 participants made up the sample, which was drawn using the incidental sampling technique. Patients were given questionnaires to complete, which were used to collect data. The information was then processed and analyzed using the Spearmen Rank. According to the study's findings, up to 78 (78%) respondents indicated they were very satisfied with the nursing services received, and up to 68 (68%) respondents felt the same. The correlation coefficient value of 0.875 indicates that there is a very strong association between service quality and patient satisfaction. Pvalue = 0.001 0.05 (P ) indicates that this relationship is significant. The level of satisfaction of BPJS patients receiving inpatient care at Salatiga Regional General Hospital is correlated with the caliber of nursing services provided. The amount of patient satisfaction rises in direct proportion to service quality.